Fiscal discipline and exchange rate regimes : evidence from the Caribbean - Duttagupta, Rupa ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 2005)
Assesses the nature of fiscal discipline under alternative exchange rate regimes.